1741PDRandomized phase II trial of CODE or AP after chemoradiotherapy for LD-SCLC: Long-term survival and toxicity analysis. (1st October 2019) - Sekine,; Harada, H; Yamamoto, N; Wakabayashi, M; Murakami, H; Goto, K; Nogami, N; Seto, T; Oshita, F; Okamoto, H; Tanaka, H; Tamura, T; et al.
Abstract: Background: The objective of this study was to select, for a phase III trial, the more promising of weekly-dose intensive chemotherapy or amrubicin plus cisplatin as subsequent therapy after induction chemoradiotherapy for previously untreated limited-disease small cell lung cancer (LD-SCLC). Methods: Patients (pts) aged 20-70 years with untreated clinical stage II/III LD-SCLC were eligible. After one cycle of accelerated hyperfractionation thoracic radiotherapy with etoposide plus cisplatin, pts without progression were randomized to either 3 cycles of cisplatin 25 mg/m 2 (days 1, 8), doxorubicin 40 mg/m 2 (day 1), etoposide 80 mg/m 2 (days 1-3), and vincristine 1 mg/m 2 (day 8) every 2 weeks (CODE) or amrubicin 40 mg/m 2 (days 1-3) and cisplatin 60 mg/m 2 (day 1) every 3 weeks (AP). The primary endpoint was the 1-year progression-free survival (PFS) after randomization. The sample size was 72 to select the arm yielding a better 1-year PFS (55% vs. 65%) with a correct selection probability of 80%. Results: From March 2011 to February 2014, 85 pts were registered. After the induction chemoradiotherapy, 75 pts were randomized to CODE (n = 39) or AP (n = 36). The one-year PFS (95% CI) was 41.0% (25.7-55.8) in the CODE arm and 54.3% (36.6-69.0) in the AP arm. Grade 4 neutropenia and grade 3 febrile neutropenia occurred in 47% and 16% in the CODE arm and 78% and 42% in the AP arm, respectively. In patients aged 61 years or older, they were noted in 48% and 19% in the CODE arm and 88% and 48% in the AP arm, respectively. In women, they were noted in 20% and none in the CODE arm and 86% and 71% in the AP arm, respectively. Grade 3 pneumonitis was noted in one patient each in both arms. Secondary malignancies developed in 4 pts in the CODE arm and 2 pts in the AP arm. The 5-year survival (95% CI) in all 85 pts was 43.2% (32.5-53.4). The 5-year survival in all pts after randomization for CODE and AP arms were 35.3% (20.6-50.2) and 45.2% (28.3-60.7), respectively. The HR (95% CI) of AP arms to CODE arm was 0.70 (0.39-1.25). Conclusions: An overall survival profile of AP was relatively good when compared to that of the historical control, but hematological toxicity was severe in AP, especially in older and female patients. Legal entity responsible for the study: JCOG. Funding: JCOG. Disclosure: All authors have declared no conflicts of interest.